2008
DOI: 10.1111/j.1365-2621.2007.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of domestic cooking on the red cabbage hydrophilic antioxidants

Abstract: The contents of vitamin C, total phenolics, anthocyanins, hydroxybenzoic and hydroxycinnamic acids as well as 2,2¢-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) monocation radical scavenging activity were evaluated in two varieties of red cabbage before and after conventional and steam-cooking. During the conventional cooking 32.7-64.5% of vitamin C and 45.7-66.9% of total phenolics were retained in cooked tissue. Decreasing cooking water volume by half led to better retention of both phenolics (by 2.7-14.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 31 publications
7
29
0
2
Order By: Relevance
“…The total phenolics content of Brassica spp. has been found to be decreased by cooking (Podsędek et al ., ; and Wachtel‐Galor et al ., ). Losses of 75, 72 and 15% of the phenolics content of turnip greens were observed after cooking at high pressure, conventional boiling and steaming, respectively (Francisco et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total phenolics content of Brassica spp. has been found to be decreased by cooking (Podsędek et al ., ; and Wachtel‐Galor et al ., ). Losses of 75, 72 and 15% of the phenolics content of turnip greens were observed after cooking at high pressure, conventional boiling and steaming, respectively (Francisco et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Podsędek et al . () also reported that boiling increased the water content of B. oleracea var. capitata rubra and that steaming slightly decreased that content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, heating condition thwat is necessary for preparation of molasses can change the structure of phenolic compounds. Some previous studies reported that TPC and subsequent antioxidant activity declined in agricultural products with increasing temperature [9][10][11][12]. On the other hand, the TPC of grape seed was found to be significantly higher when heated at 150°C for 40 minutes compared to the unheated seeds [13].…”
Section: Research Articlementioning
confidence: 86%
“…There are several studies on the effect of cooking or thermal treatment upon nutritional quality of vegetable foods. Decrease in ascorbic acid content and antioxidant capacity has been recently reported in mild heat-treated peppers (Sgroppo & Pereyra, 2009) and during domestic cooking of red cabbage (Podsędek et al, 2008). A majority of the population in India is dependent on plant foods, which provide b-carotene to meet their requirement of vitamin A.…”
Section: Introductionmentioning
confidence: 99%